Hubungan antara Kegiatan Employee Relations dengan Motivasi Kerja Karyawan - Widi Wulansari; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2022)
Abstract. It has become a basic desire to be achieved in an agency, namely the productivity of employees, so it has become a big responsibility of the agency to increase the work motivation of each employee, in order to provide optimal service to every community that has been expected. Employees themselves are an important element, also has an important influence. Therefore, the comfort of each employee is one of the main things that must be considered for the company. The purpose of this research is to determine the relationship between employee relations activities with employee motivation. This study uses quantitative methods, a research method that has been based on a philosophy of positivism. The first was to distribute questionnaires to employees of the West Bandung Regent's Office of Communication and Information Technology. Which is useful to find out what is the relationship between employee relations activities with work motivation of employees of the West Bandung Regency Government. The data collection technique determined by the author is to use total sampling. Then the data will be processed using a Likert scale whose choices use the answers: strongly agree, agree, hesitate, disagree and disagree. In distributing this questionnaire, researchers will do it online, by distributing google forms due to the pandemic situation. Researchers think that it is important to do this research with several things, namely to examine the relationship between to study the relationship of Employee Relations Activities and Work Motivation of Employees of the West Bandung Regency Government, where Employee Relations activities are very important for an agency for employee motivation, the author wants to know the truth about the relationship between Employee Relations Activities carried out for employee work motivation at the West Bandung Regency Government office. There is a significant relationship between personal calls (X1) and work motivation (Y) in West Bandung Regency employees with the strength of the relationship in the strong category. There is a significant relationship between the ballot box (X2) and work motivation (Y) in West Bandung Regency employees with the strength of the relationship being in the strong category. There is a significant relationship between entertainment and excursions (X3) and work motivation (Y) in Bandung Regency employees. West with the strength of the relationship is in the moderate category so that entertainment and field trips are carried out to build communication between communication and superiors. There is a significant relationship between sports (X4) and work motivation (Y) in West Bandung Regency employees with the strength of the relationship being in the very strong category . Abstrak. Sudah menjadi sebuah keinginan mendasar yang ingin dicapai pada sebuah intansi yaitu produktifitas dari para karyawan, sehingga sudah menjadi sebuah tanggung jawab besar dari intansi tersebut untuk meningkatkan motivasi kerja dari setiap karyawan, agar dapat memberikan adanya pelayanan yang optimal kepada setiap masyarakat yang sudah diharapkan. Karyawan sendiri merupakan sebuah elemen yang penting, juga memiliki pengaruh yang penting. Maka dari itu, kenyamanan dari setiap karyawan merupakan salah satu hal utama yang harus diperhatikan bagi perusahaan. Tujuan dilakukannya penelitian ini ialah untuk mengetahui adanya hubungan antara Kegiatan employee relations dengan motivasi kerja karyawan. penelitian ini menggunakan metode kuantitatif sebuah metode penelitian yang telah berlandaskan pada sebuah filsafah positivisme pertama dilakukannya penyebaran kuesioner diberikanpada karyawan Diskominfotik Kantor Bupati Bandung Barat. Yang berguna untuk mengetahui apa adanya hubungan antara Kegiatan employee relations dengan motivasi kerja karyawan Pemerintah Kabupaten Bandung Barat. Teknik pengumpulan data yang ditetapkan penulis adalah dengan menggunakan total sampling. Terdapat hubungan yang signifikan antara personal calls (X1) dengan motivasi kerja (Y) pada karyawan Kabupaten Bandung Barat dengan kekuatan hubungan berada dalam kategori kuat. Terdapat hubungan yang signifikan antara kotak suara (X2) dengan motivasi kerja (Y) pada karyawan Kabupaten Bandung Barat dengan kekuatan hubungan berada dalam kategori kuat ,Terdapat hubungan yang signifikan antara hiburan dan darmawisata (X3) dengan motivasi kerja (Y) pada karyawan Kabupaten Bandung Barat dengan kekuatan hubungan berada dalam kategori sedang sehingga kegiatan hiburan dan darmawisata dilaksanakan untuk membangun komunikasi antara komunikasi maupun atasan.Terdapat hubungan yang signifikan antara olahraga (X4) dengan motivasi kerja (Y) pada karyawan Kabupaten Bandung Barat dengan kekuatan hubungan berada dalam kategori sangat kuat.